2021
DOI: 10.1007/s43032-021-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Sex Does Not Impact Placental Blood Flow or Placental Amino Acid Transfer in Late Gestation Pregnant Sheep With or Without Placental Insufficiency

Abstract: Pregnant sheep have been used to model complications of human pregnancies including placental insufficiency and intrauterine growth restriction. Some of the hallmarks of placental insufficiency are slower uterine and umbilical blood flow rates, impaired placental transport of oxygen and amino acids, and lower fetal arterial concentrations of anabolic growth factors. An impact of fetal sex on these outcomes has not been identified in either human or sheep pregnancies. This is likely because most studies measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…Our study was also not powered to detect sex differences. While prior fetal sheep studies have not detected sex differences in glucose-insulin responsiveness, β-cell mass, or plasma basal insulin or IGF-1 concentrations 6,36 , this deserves further investigation. Additionally, studies are needed to evaluate the contribution of neurovascular networks and other in vivo factors that may influence fetal insulin secretion.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our study was also not powered to detect sex differences. While prior fetal sheep studies have not detected sex differences in glucose-insulin responsiveness, β-cell mass, or plasma basal insulin or IGF-1 concentrations 6,36 , this deserves further investigation. Additionally, studies are needed to evaluate the contribution of neurovascular networks and other in vivo factors that may influence fetal insulin secretion.…”
Section: Discussionmentioning
confidence: 85%
“…Common pregnancy complications impacting nutrient transfer to the fetus and resulting in fetal overgrowth or growth restriction are characterized by high or low cord blood concentrations, respectively, of insulin and IGF-1 [3][4][5] . IGF-1 is more strongly correlated with fetal weight than insulin 4,6,7 . Fittingly, IGF-1 has been studied in sheep as a fetal intervention for growth restriction [8][9][10] .…”
Section: Introductionmentioning
confidence: 92%
“…This would imply a depletion of normal energy usage pathways and use of alternative metabolic pathways for fetal energy as glucose, lactate and amnio-acids are all major sources of fetal nutrition (Kyllo et al, 2023). In states of impaired fetal oxygenation, such as placental insufficiency, the consumption of these energy sources change, with an overall decrease in glucose and an increase in lactate (Brown et al, 2022;Cetin et al, 2020;Thorn et al, 2013). Further, in states of fetal hypoxemia or significant stress, there is a consumption of available glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is required to determine whether fetal sex is a significant contributing factor in the regulation of fetal myocyte proliferation and maturation. We have recently found that in the late gestation fetal sheep, with and without placental insufficiency, fetal sex does not influence placental AA transfer or blood flow ( 54 ).…”
Section: Discussionmentioning
confidence: 99%